2001
DOI: 10.1098/rspb.2000.1345
|View full text |Cite
|
Sign up to set email alerts
|

Primer effects of a brood pheromone on honeybee behavioural development

Abstract: Primer pheromones are thought to act in a variety of vertebrates and invertebrates but only a few have been chemically identi¢ed. We report that a blend of ten fatty-acid esters found on the cuticles of honeybee larvae, already known as a kairomone, releaser pheromone and primer pheromone, also act as a primer pheromone in the regulation of division of labour among adult workers. Bees in colonies receiving brood pheromone initiated foraging at signi¢cantly older ages than did bees in control colonies in ¢ve ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
124
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 28 publications
1
124
1
1
Order By: Relevance
“…These results suggested that the worker inhibitory factor was either a nonvolatile ''contact'' pheromone, a behavior, or both, with old bees having greater inhibitory potency than younger bees. The possibility that the worker inhibitory factor might be a pheromone gained strength with the discovery that two other honey bee primer pheromones, queen mandibular pheromone (QMP) and brood pheromone (BP), also play a role in regulating worker behavioral maturation (11,12). In addition, Pankiw (13) recently reported that a hexane extract of foragers delays age at onset of foraging.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggested that the worker inhibitory factor was either a nonvolatile ''contact'' pheromone, a behavior, or both, with old bees having greater inhibitory potency than younger bees. The possibility that the worker inhibitory factor might be a pheromone gained strength with the discovery that two other honey bee primer pheromones, queen mandibular pheromone (QMP) and brood pheromone (BP), also play a role in regulating worker behavioral maturation (11,12). In addition, Pankiw (13) recently reported that a hexane extract of foragers delays age at onset of foraging.…”
mentioning
confidence: 99%
“…Exposure to QMP and BP was controlled in these experiments because both can affect age at onset of foraging (11,12). Instead of a live queen each colony was given a commercially available plastic strip (Bee Boost, PheroTech, Vancouver, Canada) containing the five-component QMP blend (2) that releases one queen equivalent per day.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the food flow, the better the queen is feeded, stimulating it to increase the egg laying rate and, consequently, offspring production, colony population size and number of forage workers (LE CONTE et al, 2001 ;. The offspring stimulate the foraging for food resources in general, thus the amount of pollen and nectar (honey) collected by a colony of Apis mellifera depends on the amount of forage workers and the offspring (eggs, larvae and pupae) present in this colony, and these two variables depends on the population size of the colony .…”
Section: Resultsmentioning
confidence: 99%